2016
DOI: 10.1681/asn.2015020210
|View full text |Cite
|
Sign up to set email alerts
|

Nephrin Contributes to Insulin Secretion and Affects Mammalian Target of Rapamycin Signaling Independently of Insulin Receptor

Abstract: Nephrin belongs to a family of highly conserved proteins with a well characterized function as modulators of cell adhesion and guidance, and nephrin may have a role in metabolic pathways linked to podocyte and pancreatic b-cell survival. However, this role is incompletely characterized. In this study, we developed floxed nephrin mice for pancreatic b-cell-specific deletion of nephrin, which had no effect on islet size and glycemia. Nephrin deficiency, however, resulted in glucose intolerance in vivo and impair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 56 publications
2
29
0
Order By: Relevance
“…Mice depleted of nephrin in b cells showed no change in body weight and random glycemia or random plasma insulin levels but presented glucose intolerance in vivo and impaired glucose-stimulated release of insulin ex vivo. 12 The absence of pancreatic nephrin had no effect on the size or number of the islets or the b cell mass, and the mice did not develop diabetes. 12 Interestingly, Fornoni and colleagues 12 observed that eight patients with mutations in NPHS1 showed glucose intolerance compared with nine healthy controls and three patients with other genetic forms of nephrotic syndrome.…”
mentioning
confidence: 92%
See 4 more Smart Citations
“…Mice depleted of nephrin in b cells showed no change in body weight and random glycemia or random plasma insulin levels but presented glucose intolerance in vivo and impaired glucose-stimulated release of insulin ex vivo. 12 The absence of pancreatic nephrin had no effect on the size or number of the islets or the b cell mass, and the mice did not develop diabetes. 12 Interestingly, Fornoni and colleagues 12 observed that eight patients with mutations in NPHS1 showed glucose intolerance compared with nine healthy controls and three patients with other genetic forms of nephrotic syndrome.…”
mentioning
confidence: 92%
“…12 The absence of pancreatic nephrin had no effect on the size or number of the islets or the b cell mass, and the mice did not develop diabetes. 12 Interestingly, Fornoni and colleagues 12 observed that eight patients with mutations in NPHS1 showed glucose intolerance compared with nine healthy controls and three patients with other genetic forms of nephrotic syndrome. This is in contrast to a previous observation by Kuusniemi et al, 9 who addressed the function of b cells by oral glucose tolerance test in patients with NPHS1 who had received a kidney transplant 1-5 years earlier.…”
mentioning
confidence: 92%
See 3 more Smart Citations